2017
DOI: 10.5713/ajas.17.0053
|View full text |Cite
|
Sign up to set email alerts
|

In ovo vaccination using Eimeria profilin and Clostridium perfringens NetB proteins in Montanide IMS adjuvant increases protective immunity against experimentally-induced necrotic enteritis

Abstract: ObjectiveThe effects of vaccinating 18-day-old chicken embryos with the combination of recombinant Eimeria profilin plus Clostridium perfringens (C. perfringens) NetB proteins mixed in the Montanide IMS adjuvant on the chicken immune response to necrotic enteritis (NE) were investigated using an Eimeria maxima (E. maxima)/C. perfringens co-infection NE disease model that we previously developed.MethodsEighteen-day-old broiler embryos were injected with 100 μL of phosphate-buffered saline, profilin, profilin pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…Importantly, they can provide robust and early protection against immune suppressive diseases such as infectious bursal disease [ 81 , 82 ] and vaccines against multiple diseases have been successfully combined. For instance, studies have shown that in-ovo vaccination strategies can simultaneously confer protective immunity against Marek’s disease, infectious bursal disease, Newcastle disease, fowl poxvirus, coccidiosis, and necrotic enteritis [ 83 , 84 ]. Other combination vaccines under investigation include vectored vaccines that simultaneously provide protection against Newcastle disease and infectious bursal disease [ 85 ].…”
Section: New Approaches For the Development Of Veterinary Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, they can provide robust and early protection against immune suppressive diseases such as infectious bursal disease [ 81 , 82 ] and vaccines against multiple diseases have been successfully combined. For instance, studies have shown that in-ovo vaccination strategies can simultaneously confer protective immunity against Marek’s disease, infectious bursal disease, Newcastle disease, fowl poxvirus, coccidiosis, and necrotic enteritis [ 83 , 84 ]. Other combination vaccines under investigation include vectored vaccines that simultaneously provide protection against Newcastle disease and infectious bursal disease [ 85 ].…”
Section: New Approaches For the Development Of Veterinary Vaccinesmentioning
confidence: 99%
“…In-ovo vaccination strategies have also been explored for other poultry diseases with promising results. This included an avian influenza vaccine based on a non-replicating human adenovirus vector [ 86 ], a recombinant viral vector vaccine against infectious laryngotracheitis [ 87 ], recombinant protein Eimeria vaccines [ 84 , 88 , 89 ] and a fowl adenovirus vectored vaccine against inclusion body hepatitis [ 90 ], among many others. A Mycoplasma gallisepticum vaccine for in-ovo vaccination of layer chickens has also recently been evaluated, even though high chick losses at hatch were reported for the medium and high doses of the vaccine that were investigated [ 91 ].…”
Section: New Approaches For the Development Of Veterinary Vaccinesmentioning
confidence: 99%
“…Profilin (3-1E) is a conserved surface antigen of both merozoites and sporozoites, and it can also act as an anticoccidial adjuvant ( Lee et al., 2010 , 2012 ; Zhang et al., 2012 ). Profilin is able to induce cell-mediated protective immunity against Eimeria species ( Lillehoj et al., 2017 ; Tang et al., 2018 ). Compared with profilin, the oocyst output of rEt-M2AP–immunized chickens were lower ( Ma et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Profilin is a conserved surface antigen of both merozoites and sporozoites that can induce cell-mediated immunity against live Eimeria stages ( Tang et al., 2018 ). Profilin also induced protective immunity against E. tenella in chickens ( Lillehoj et al., 2017 ), both when used as an anticoccidial vaccine candidate and when applied as an adjuvant ( Gowen et al., 2006 ; Lee et al., 2011 ; Lillehoj et al., 2017 ; Bussière et al., 2018 ). EtSAG4 is specifically expressed in the second-generation merozoite stage of E. tenella ( Tabarés et al., 2004 ), and it was able to protect chickens against an E. tenella challenge; thus, EtSAG4 might be a candidate gene for use in a vaccine against coccidiosis ( Tabarés et al., 2004 ; Zhao et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Profilin or Eimeria 3-1E is a conserved surface antigen of both merozoites and sporozoites of E. acervulina, E. tenella, and E. maxima. Profilin encodes a 170 aa open reading frame which are expressed in the invasive, sporozoitic, and merozoitic stages of Eimeria (Zhang et al 2012;Lillehoj et al 2017). The recombinant protein has successfully induced cell-mediated immunity against live Eimeria species, as illustrated by Tang et al (2018b) who reported an enhanced protective immunity against E. tenella in birds immunized with Et-EmPro expressing profilin cloned from E. maxima compared to the wild type.…”
Section: Identification and Application Of Novel Antigensmentioning
confidence: 99%